2022
DOI: 10.3389/fphar.2022.1008946
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, randomized controlled trial of traditional Japanese medicine, kakkonto with shosaikotokakikyosekko, for mild and moderate coronavirus disease patients

Abstract: The traditional Japanese (Kampo) medicine, kakkonto with shosaikotokakikyosekko, has antiviral and anti-inflammatory effects. In this randomized trial, patients with mild and moderate coronavirus disease (COVID-19) were randomly allocated to the control group receiving conventional treatment for symptom relief such as antipyretics and antitussives or the Kampo group receiving mixed extract granules of kakkonto (2.5 g) and shosaikotokakikyosekko (2.5 g) three times a day for 14 days in addition to conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…While some papers have described the effectiveness of Kampo for the treatment of COVID-19, very few reports are available regarding administering Kampo to pregnant women infected with the virus [2][3][4]11]. Although Kampo has been established for at least 1800 years, the safety of Kampo in pregnant women remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some papers have described the effectiveness of Kampo for the treatment of COVID-19, very few reports are available regarding administering Kampo to pregnant women infected with the virus [2][3][4]11]. Although Kampo has been established for at least 1800 years, the safety of Kampo in pregnant women remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Kampo is a cost-effective and safe medication that is covered by insurance in Japan. Several studies regarding the treatment of COVID-19 with Kampo medicine have previously been published [2][3][4]. In a previous study, we have also reported a methodology and cases of the effectiveness of shoseiryuto (SST) in treating pregnant women infected with COVID-19 [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, three cases of COVID-19 pneumonia were successfully treated with SKT in combination with other drugs [3]. Very recently, treatment with kakkon-to, and sho-saiko-to-ka-kikyo-sekko that contains saikosaponin as a component, was reported to be effective for fever relief with suppression of disease progression in COVID-19 patients [11]. Therefore, Kampo medicines other than SKT, that contain saikosaponin, could be efficacious against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19-confirmed patients, the risk of illness worsening in the Kampo group tended to be lower than that in the non-Kampo group after adjusting the staging of COVID-19, and within four days from the onset it was significantly lower in the Kampo group than in the non-Kampo group. In the RCT, patients with mild and moderate COVID-19 were randomly allocated to the control group receiving conventional treatment for symptom relief such as antipyretics and antitussives, or the Kampo group receiving mixed extract granules of kakkonto and shosaikotokakikyosekko in addition to conventional treatment [5]. In all, 161 patients were randomly assigned to the Kampo group (n = 81) or the control group (n = 80).…”
mentioning
confidence: 99%